The Implementation of a Chatbot and Website Interface in Department of Development Economic - Mulyadi, Rizki; Rosnita, Lidya; Rachman, Aulia; Azhari, Muhammad (Department of Informatics, Universitas Malikussaleh, 2025)
The issue arising from this activity is the need to optimize the existing CMS Joomla-based website to make it more responsive and interactive in line with modern technological developments. The update was carried out using SP Page Builder as the main tool for interface development, while the chatbot was implemented using JavaScript technology with the Levenshtein Distance algorithm to provide automatic information services to users. The result of this practical work includes updates to several key components of the website, including the homepage, which is now equipped with a dynamic banner, a message from the head of the department, highlights of the study program, and a news and announcement section. The faculty and staff pages have been optimized with more comprehensive information, while the gallery page has been redesigned with a responsive grid layout. The chatbot implementation successfully provides automated information services for common academic questions, such as class schedules, KRS (course registration), and scholarships. Overall, these updates have improved the accessibility of information and the user experience in accessing the Deparment of Development Economics website.